미국 캘리포니아 쌀 산업의 구조와 변화 - 최정섭 (한국농촌경제연구원, 2009)
Commercial production of rice in California will mark the 100th year in 2012. With desirable soil conditions, water supply from the Sierra mountains, research support jointly by the University of California and the industry, and the market development efforts, the rice industry in California has developed into an important regional agricultural industry in the Sacramento and San Joaquin Valley areas. California produces twenty-two percent of total U.S. rice. Most rice produced in California is Japonica type, which is staple food in Korea, Japan, and Taiwan. About thirteen hundred farms produce 1,800 to 2,160 thousand metric tons of rice annually in California. The record high level of yields per 10a (are) and cultivated area has reached 900kg and 240 thousand ha (hectare), respectively. Per capita consumption of rice in the U.S. is on the rise. The largest outlet is exporting to foreign markets followed by table rice and manufacturing. Some elements comprise the opportunities and challenges for the California rice industry. In international markets, the disappearance of Australia as a major competitor caused by severe drought and domestic difficulties in Egypt and China put the competitiveness of California rice at a stronger position. However, there are several challenges facing the California rice industry. The future availability of enough water is one of the most serious problems. Other challenges include the environmental issues related to the pesticide use and GHG emission-related restrictions. Additional challenges worth mentioning would be the staggering yield-increasing technology development and the continuation of farm programs supporting farm incomes. After reaching the record high level in April, 2009, the international price of Japonica type rice has started to decline. It followed the pattern of Indica type rice price movements with a gap of almost full year. It is difficult to forecast the price, but the Japonica rice price will not decrease down to the level that prevailed before the price hike. Higher international prices enhance the relative competitiveness of Korean rice. It seems to be a good opportunity to pursue ways to export its high-quality Japonica rice.